A compilation of moored current meter observations volume III - Webster, Ferris; Fofonoff, Nicholas P. (Woods Hole Oceanographic Institution, 1967)
Originally issued as Reference No. 67-66, series later renamed WHOI-. Summaries of current measurements made with Richardson current meters in two regions of the Western North Atlantic are presented. Averaged quantities are presented in the form of computer-plotted curves. Submitted to the Office of Naval Research under Contract Nonr-3351(00) NR 083-501 and NR-2196(00) NR 083-004.